MEASURING RESULTS OF PROJECT MANAGEMENT TRIANGLE CONSTRAINTS: THE CASE OF ENGINEERING BUILDING AT EFFAT UNIVERSITY - Salma Al-Qahtani; Mohamed Baymout (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
This study aimed to determine delay factors in delivering Engineering building and gaps in the project management in Effat University. The study had used quantitative research. The respondents were Effat University student and faculty staff. Data collection techniques to be adopted were interviewed respondent and survey. Secondary data comprise of an assortment of articles from published and peer reviewed books and journals included reliable web sources that enclosed information on operation management. The sample was conducted used convenience sampling technique. The questionnaire was presented to Effat University student. The data was gathered by employed normal questionnaire. The questionnaires had open and closed ended queries created for writing and three segments were created. First segments were concerned with information included respondent distribution. Meanwhile, second segment related to data analysis and discussion from the questionnaire contained subsections. The descriptive statics in term of percentage included frequency distribution were qualitative. There were five factors that influenced delay in delivering the building included clement and seasonality, financial difficulties, cleanliness and orderliness, short time planning phase and project scope limitation among contractor